Magnets and school turnarounds: Revisiting policies for promoting equitable, diverse schools - Ayscue, Jennifer B.; Siegel-Hawley, Genevieve (Education Policy Analysis Archives, 2019)
This case study examines how magnet school and school turnaround processes can work together to promote desegregation and improvement. Based on cross-case analysis of three magnet schools undergoing turnarounds, this study draws on data from the 2010 federal Magnet Schools Assistance Program grant and qualitative fieldwork through observations, interviews, and focus groups. In academically struggling schools with high concentrations of students of color and low-income students, successful magnet turnarounds involve changes across many aspects of the schools. While the local context is essential for shaping the magnet turnaround process, these three schools reveal common ways in which participants viewed their schools as successful turnarounds, the elements that supported success, and the challenges that magnets undergoing a turnaround are likely to face. Participants’ perceptions of a successful turnaround were based on increasing family interest and increasing racial and economic diversity, as well as improvements in curriculum and instruction, school culture, and academic achievement. This study helps broaden our definition of a school turnaround beyond higher test scores and reminds us of the origins of the concept, which revolved around desegregation. Lessons from the sites suggest that rather than closing underperforming or under-enrolled schools, districts should consider magnet schools as a turnaround approach.